Conformational Dynamics of Ago-Mediated Silencing Processes - Willkomm, Sarah (Int J Mol Sci, 2015)
Argonaute (Ago) proteins are key players of nucleic acid-based interference mechanisms. Their domains and structural organization are widely conserved in all three domains of life. However, different Ago proteins display various substrate preferences. While some Ago proteins are able to use several substrates, others are limited to a single one. Thereby, they were demonstrated to act specifically on their preferred substrates. Here, we discuss mechanisms of Ago-mediated silencing in relation to structural and biochemical insights. The combination of biochemical and structural information enables detailed analyses of the complex dynamic interplay between Ago proteins and their substrates. Especially, transient binding data allow precise investigations of structural transitions taking place upon Ago-mediated guide and target binding.